GAYA KEPEMIMPINAN TRANSFORMASIONAL UPAYA DAN SOLUSI - Astohar, Bapak; Siswoko, Bapak (STIE Totalwin Semarang, 2010)
Most of conflicts between subordinary and leader happened because of leadership style that not aceptable with subordinary. Subordinary often judge that their leader who manage the organization have an otoriter and straight behaviour, they never think aboutÂ and subordinary needs. Organization must be adapt with the best leadership style for them. Leader have toÂ implementation leadership style types that suitable for the organization. This transformational leadership style could be sthrength from trust crisis for leadership in the company